2021
DOI: 10.1002/etc.4995
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Addition, Independent Action, and Quantitative Structure–Activity Relationships for Chemical Mixture Toxicities of the Disinfection By products of Haloacetic Acids on the Green Alga Raphidocelis subcapitata

Abstract: The potential toxicity of haloacetic acids (HAAs), common disinfection by products (DBPs), has been widely studied; but their combined effects on freshwater green algae remain poorly understood. The present study was conducted to investigate the toxicological interactions of HAA mixtures in the green alga Raphidocelis subcapitata and predict the DBP mixture toxicities based on concentration addition, independent action, and quantitative structure–activity relationship (QSAR) models. The acute toxicities of 6 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The QSAR models had higher R 2 and lower RMSE than the CA and IA models, which indicated that the quality of the QSAR model was stronger compared to the CA and IA models. Several studies have indicated that the predictive ability of the QSAR model in determining the toxicity of mixtures surpasses that of the CA and IA models. …”
Section: Resultsmentioning
confidence: 99%
“…The QSAR models had higher R 2 and lower RMSE than the CA and IA models, which indicated that the quality of the QSAR model was stronger compared to the CA and IA models. Several studies have indicated that the predictive ability of the QSAR model in determining the toxicity of mixtures surpasses that of the CA and IA models. …”
Section: Resultsmentioning
confidence: 99%
“…32,33 The MDR is the ratio of the concentration addition or independent action predicted value (EC x,Pred ) and the observed effect concentration (EC x,Obs ) as shown in equation 6. 34 Note: α and β is the position and slope parameters, respectively; R 2 means the maximum determination coefficient; RMSE respects the minimum root mean square error; pEC 50 is the negative logarithm 50% effect concentration; NOEC is the no observed effect concentration.…”
Section: Toxicity Interaction Analysismentioning
confidence: 99%